An An Analysis of Students’ Learning Outcome of English for Math and Science Course - Rosnaningsih, Asih (Fakultas Keguruan dan Ilmu Pendidikan Universitas Faletehan, 2024)
This research aims to analyze the learning outcome of English language learning in higher education, particularly in the context of English for Mathematics and Science course. This research employs a qualitative case study methodology to explore students’ learning outcomes and their language barriers faced by students during learning it. It also discusses the teaching materials, learning activities and teaching approaches used in EFMS courses. The subjects of this research are three classes from the sixth semester students of primary teacher education program of University of Muhammadiyah Tangerang with total amount of 78 students and one lecturer. The data collecting techniques used were observation, interview and documentation. The result found that students’ learning outcome are mostly 55% got the “A - excellent” grade (43 students), 27% got the “B - good” grade (21 students), 11,5% got the “C - adequate” grade (9 students), and 6,4% got the “D - Failed” (5 students). Within this result, there were many students who performed well and can follow the course until the end of the meeting and understand the material comprehensively, but it cannot be avoided that notable language barriers that impacted their learning outcome, particularly when learning English for Mathematics and Science. These language difficulties were exacerbated by the complexity of the subject matter, as students often struggled to grasp both the technical content and the English terminology simultaneously.